2019
DOI: 10.1016/j.molmet.2019.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine decarboxylase is critical for the maintenance of skeletal muscle mitochondrial integrity and muscle mass

Abstract: Objective Phosphatidylethanolamine (PtdEtn) is a major phospholipid in mammals. It is synthesized via two pathways, the CDP-ethanolamine pathway in the endoplasmic reticulum and the phosphatidylserine (PtdSer) decarboxylase (PSD) pathway in the mitochondria. While the CDP-ethanolamine pathway is considered the major route for PtdEtn synthesis in most mammalian tissues, little is known about the importance of the PSD pathway in vivo, especially in tissues enriched with mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
(48 reference statements)
0
20
1
Order By: Relevance
“…The changes in phospholipid composition were associated with reduced type IIb myofiber size in aged muscle (Uchitomi et al, 2019), which is similar to our findings revealing a negative association between phospholipids (PC, PE, and PG) with muscle volume. While in contrast to recent reports that showed reducing PE levels in skeletal muscle by inhibiting key phospholipid synthesis pathways (phosphatidylserine decarboxylase) results in muscle atrophy (Heden et al, 2019; Selathurai et al, 2019), our findings and those by Uchitomi et al (2019) reveal that age‐induced muscle atrophy may be linked to elevated phospholipids levels in skeletal muscle.…”
Section: Discussioncontrasting
confidence: 99%
“…The changes in phospholipid composition were associated with reduced type IIb myofiber size in aged muscle (Uchitomi et al, 2019), which is similar to our findings revealing a negative association between phospholipids (PC, PE, and PG) with muscle volume. While in contrast to recent reports that showed reducing PE levels in skeletal muscle by inhibiting key phospholipid synthesis pathways (phosphatidylserine decarboxylase) results in muscle atrophy (Heden et al, 2019; Selathurai et al, 2019), our findings and those by Uchitomi et al (2019) reveal that age‐induced muscle atrophy may be linked to elevated phospholipids levels in skeletal muscle.…”
Section: Discussioncontrasting
confidence: 99%
“…Phosphoethanolamine is an ethanolamine derivate produced as an intermediate of the CDP-ethanolamine pathway involved in the metabolism of glycerophospholipid and biological membrane turnover (Patel and Witt, 2017 ; van der Veen et al, 2017 ). Disruption of CDP-ethanolamine pathway has been associated with mitochondrial dyshomeostasis in mouse models of muscle atrophy (Selathurai et al, 2019 ) and insulin resistance (Funai et al, 2016 ). Phosphoethanolamine has also been found to mediate mitochondrial membrane fusion and curvatures and, in combination with ethanolamine, to promote autophagy and longevity (Rockenfeller et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tasseva et al reported a reduced mitochondrial pool of PE in CHO PISD knockdown cells, characterized by a fragmented mitochondrial network [12]. Furthermore, PSD knockdown expression in the skeletal muscle of mice was responsible for the decrease in PE content and rise in PS with myopathy development [16]. Therefore, we hypothesized that PSD could play a role in the proposed mitochondrial membrane effects of DXR.…”
Section: Introductionmentioning
confidence: 89%